Analisis Kesiapan Berubah Dalam Rangka Transformasi Digital - Jane, Orpha; Shelvi, Shelvi (Business Education Program of Universitas Pendidikan Indonesia, 2022)
The aim of this research was to identify teachers and students readiness to change and to measure specifically their readiness to adapt digital technology. This research used survey method and the unit of analysis are teachers and students registered in X school. The data was collected from interview and questionnaire that has been distributed to 326 students and 21 teachers. Data analysis used descriptive statistic to measure their readiness to change. The result of this research indicate that both teachers and students were not ready if X school intended to do digital transformation. From the results of data processing, it is also found that there are differences in perceptions between teachers and students that must be overcome by the school if it plans to adopt digital learning in the future.